MOTIVASI MEMEDIASI PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA DOSEN PADA UNIVERSITAS MAYJEND SUNGKONO MOJOKERTO - Putri, Rainy Alifa Rifa Febrianti; Prasetyo, Indra; Utari, Woro (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This study aims to determine the effect of work environment and communication on lecturer performance with motivation as a moderating variable. The object of this research is all lecturers at the University of Mayjend Sungkono Mojokerto. The sample in this study used total sampling, namely all lecturers at the University of Mayjend Sungkono Mojokerto. This study uses primary data by distributing questionnaires directly to 60 respondents. This study uses the Partial Least Square (PLS) approach using the SmartPLS Version 3.0 application. The results showed that the work environment and communication had a positive and significant effect on lecturer performance, the work environment and communication had a positive and significant effect on motivation but motivation had no effect on lecturer performance. The results of the indirect effect show results if motivation mediates the influence of the work environment and communication on lecturer performance.